2017
DOI: 10.1002/ird.2103
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of River Flow Regime Changes Related to Water Availability on the Kapuas River, Indonesia

Abstract: Rivers are major sources of fresh water, which is a basic need in society. The availability of water is affected by river basin characteristics such as rainfall and land cover type. Along with population and economy growth, there has been a change in land use that leads to changes in land cover types, thereby changing the river flow regime and affecting the availability of water in the river. Thus it is necessary to analyse water flow regime changes in the river to determine water availability for proper actio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…At the same time, the Kapuas River stream has yet to be obstructed by manmade flow control structures (Kästner and Hoitink, 2019) and is still poorly gauged. Additionally, satellite image interpretation during the period from 1990 until 2012 also showed that significant changes in land use have occurred in Kapuas River Basin (Herawati et al, 2018). These changes were mainly inflicted by the increasing land use for open land and plantations and decreasing areas of swamp forest and primary dry forest.…”
Section: Introductionmentioning
confidence: 96%
“…At the same time, the Kapuas River stream has yet to be obstructed by manmade flow control structures (Kästner and Hoitink, 2019) and is still poorly gauged. Additionally, satellite image interpretation during the period from 1990 until 2012 also showed that significant changes in land use have occurred in Kapuas River Basin (Herawati et al, 2018). These changes were mainly inflicted by the increasing land use for open land and plantations and decreasing areas of swamp forest and primary dry forest.…”
Section: Introductionmentioning
confidence: 96%
“…The effect of climate change on the probability distribution of monsoon flood tragedies Most researchers found that the responsiveness of the hydrological and geomorphological systems is as important for flood phenomena as climate change. What is still unclear is how flood phenomena along river basins relate to climate and river characteristics and which is dominant [ [26] , [27] , [28] ]. This research also included the analysis of the local rainfall pattern used as one of the climate factors in particular areas, such as the Pahang River Basin, to identify the main cause of the changes in the river planform.…”
Section: Introductionmentioning
confidence: 99%
“…Island, yet spreads to other Indonesia's wet tropical areas such as Sumatra (Taufik, 2010;Yuono et al, 2020) and Kalimantan (Herawati et al, 2018;Taufik et al, 2017), which led to the hydrometeorological disasters such frequent fires (Purnomo et al, 2021;Tan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%